A systems thinking approach to eliminate delays on building construction projects in South Africa - Aiyetan, Olatunji; Smallwood, John; Shakantu, Winston (University of the Free State, 2011)
It is obvious that the performance of firms and their market competitiveness hinge on project delivery time. Many approaches have been used to reduce the effect of the potential factors of delay on project delivery time. In this study, the systems approach has been employed and validated. Inferential statistical analysis was conducted to analyse eighty-eight questionnaires returned during the primary study and twenty-four during the validation phase. The holistic role of professionals in the construction industry was illustrated with the aid of causal loop analysis, showing cause and effect relationships. Based on the findings that eight out of the twelve categories of problems of delays are construction-related, the study identified seven stages of construction project delivery and various activities in these stages that could reduce the negative influence of delay factors on project delivery time. The interventions category, which has the most influence on the elimination of delays in project delivery, occurs during the construction stage, followed by interventions during the briefing/design stage. The interventions category with the least influence is pre-qualification of suppliers. The study recommends that adequate planning, pre-qualification of suppliers, provision of work schedule, and prompt payment of interim certificates be focused on to mitigate delays in project delivery time. Furthermore, the following courses should be included in all built-environment education programmes: operational planning; quality; design, and generic management.

Dit is duidelik dat die prestasie van firmas en hul markmededingbaarheid om projek-voltooiingstyd draai. Baie benaderings is al gevolg om die effek van die potensiële faktore van vertraging op projek-voltooiingstyd te verminder. In hierdie studie is die sisteembenadering gebruik en gevalideer. Inferensiële statistiese analise is gebruik om die agt-en-tagtig vraelyste teruggestuur gedurende die primêre studie en vier-en-twintig gedurende die validasiestadium te bestudeer. Die holistiese rol van professionele persone in die konstruksie-industrie is geïllustreer met die hulp van oorsaaklike lusanalise wat gevolg en effek-verhoudings aandui. Gebaseer op die bevinding dat agt van die twaalf kategorieë van probleme van vertragings met konstruksie verband hou, het die studie sewe fases van konstruksie projekvoltooiingstyd asook verskeie aktiwiteite in hierdie fases geïdentifiseer wat die negatiewe invloede van vertragingsfaktore op projekvoltooiingstyd verminder. Die intervensieskategorieë wat die meeste invloed op die eliminasie van vertragings van projekvoltooiings gehad het, is dié gedurende die konstruksiestadium, gevolg deur intervensies gedurende die opdrag-/ontwerpstadium. Die intervensieskategorie met die minste invloed is pre-kwalifikasie van verskaffers. Die studie beveel aan dat daar genoeg gefokus moet word op beplanning, pre-kwalifikasie van verskaffers, voorsienning van werkskedule, en vinnige betaling van tussentydse sertifikate om vertragings in projekvoltooiingstyd te verminder. Verder, behoort die volgende kursusse in alle bou-omgewingsonderrigprogramme ingesluit te word: operasionele beplanning, kwaliteit, ontwerp en generiese bestuur.
Keywords: Systems thinking; Building construction projects; South Africa